A106 SAFETY OF USTEKINUMAB WITH AND WITHOUT CONCOMITANT CORTICOSTEROIDS OR IMMUNOSUPPRESSANTS IN PATIENTS WITH MODERATELY-TO-SEVERELY ACTIVE CROHN'S DISEASE. (1st March 2018) - Sands, B E; Gasink, C; Jacobstein, D; Ott, E; Lang, Y; Ramachandran, P; Ghosh, S
Abstract: Background: Ustekinumab (UST), a monoclonal antibody to IL-12 and 23, was recently approved for the treatment of moderate-severe CD. Aims: Here we report safety data with and without concomitant use of Immunomodulators(IMM) and corticosteroids(CS) in induction and maintenance in pts pooled from the Phase 2 and 3 CD studies. Methods: Percentages of pts experiencing safety events (AEs, SAEs, infections, and deaths) were assessed with and without concomitant IMM or CS use at baseline after IV ustekinumab (UST) or placebo (PBO) induction (8 weeks) and were then also compared with SC UST or PBO maintenance (up to 44 weeks) from the Phase 2 and 3 CD clinical studies. Pts who received IV UST (doses included: 130mg flat dose and 1, 3, 4.5, & 6 mg/kg) during the PBO-controlled induction period (Week 0–8) were pooled from 2 Phase 2 (C0379T07 & CERTIFI) and 2 Phase 3 (UNITI-1 and 2) clinical studies (total n= 1, 986). For maintenance, SC UST (combining 90mg q8w and q12w) and PBO were pooled and compared in the randomized responder populations (ie responders to IV UST induction) from the maintenance phase of the Phase 2 CERTIFI (Week 8 to Week 22) and Phase 3 IM-UNITI (Week 0 to Week 44) studies (total n= 541). Results: No death occurred in either the induction or maintenance phases in any groups. Through 8 weeks of induction, the percentages of pts with AEs, SAEs, and infections were similar between UST and PBO both on and off IMM and CS: across all 4 subgroups, for UST, 58–63% had AEs, 4–7% had SAEs, and 19–23% had infections and for PBO, 56–66% had AEs, 5–9% had SAEs, and 21–26% had infections. In maintenance, proportions of pts experiencing AEs, SAEs, and infections were generally similar between UST and PBO groups both on and off IMM and CS, : across all 4 subgroups, for UST, 72–82% had AEs, 9–10% had SAEs, and 41–43% had infections and for PBO, 77–87% had AEs, 9–15% had SAEs, and 37–49% had infections. Proportions of pts on CS in both the UST and PBO groups experienced slightly higher rates of AEs compared with those not on CS (UST, 82% vs 74%, respectively; PBO, 87% vs 76%, respectively).Additionally, PBO pts on CS also experienced slightly higher rates of SAEs (15%) and infections (49%) than the other groups (9–12% with SAEs; 37–43% with infections). Conclusions: No differences in safety data were identified based on the use of concomitant IMMs or CSs in UST-treated pts with either IV induction or with SC maintenance compared to PBO. The concomitant use of IMM or CS during either IV induction or SC maintenance treatment with UST did not adversely impact the previously reported favorable safety profile of UST in moderate to severe CD pts, although concomitant CS did result in slightly higher rates of events during maintenance, particularly in the PBO group. Funding Agencies: Janssen Research & Development, LLC funded this study